Correlation between Socioeconomic Level and Oral Health Related Quality of Life in Egyptian Schoolchildren: An Observational Cross-sectional Study - Dehis, Heba; Sweidan, Ayman T. (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: This observational and cross-sectional study aimed to assess the orthodontic treatment need, oral health-related quality of life (OHRQoL), and self-esteem in relation to socioeconomic level as well as investigate the incidence of malocclusion and orthodontic treatment need in Egyptian school children. MATERIALS AND METHODS: Three hundred and twenty-four schoolchildren from governmental, private, and international schools representing different socioeconomic levels ranging from 11 to 14 years were recruited. Self-esteem and OHRQoL were measured using validated questionnaires. Clinical examination was used to assess the orthodontic treatment need represented by the index of orthodontic treatment need (IOTN) score as well as Angle’s classification of occlusion. RESULTS: International schools showed the lowest total IOTN scores than governmental and private schools (p = 0.031). Governmental scores showed the statistically significantly highest mean CPQ11-14 score (Worst OHR-QOL) followed by private schools then international schools (p = 0.035). There was no statistically significant difference between Angle’s classes of malocclusion as well as self-esteem between the three different socioeconomic level groups. CONCLUSION: Lower socioeconomic status (SES) was associated with higher orthodontic treatment need according to the total IOTN score and worst OHRQoL. Socioeconomic status did not affect the distribution of malocclusion according to Angle’s classification nor did it affect self-esteem.